Summary of the ISEV workshop on extracellular vesicles as disease biomarkers, held in Birmingham, UK, during December 2017. Issue 1 (17th May 2018) - Clayton, Aled; Buschmann, Dominik; Byrd, J. Brian; Carter, David R. F.; Cheng, Lesley; Compton, Carolyn; Daaboul, George; Devitt, Andrew; Falcon‐Perez, Juan Manuel; Gardiner, Chris; Gustafson, Dakota; Harrison, Paul; et al.
ABSTRACT: This report summarises the presentations and activities of the ISEV Workshop on extracellular vesicle biomarkers held in Birmingham, UK during December 2017. Among the key messages was broad agreement about the importance of biospecimen science. Much greater attention needs to be paid towards the provenance of collected samples. The workshop also highlighted clear gaps in our knowledge about pre‐analytical factors that alter extracellular vesicles (EVs). The future utility of certified standards for credentialing of instruments and software, to analyse EV and for tracking the influence of isolation steps on the structure and content of EVs were also discussed. Several example studies were presented, demonstrating the potential utility for EVs in disease diagnosis, prognosis, longitudinal serial testing and stratification of patients. The conclusion of the workshop was that more effort focused on pre‐analytical issues and benchmarking of isolation methods is needed to strengthen collaborations and advance more effective biomarkers.